An experimental investigation of vapor generatorcharacteristics in a low-pressure turbine engine - Pattanachok Saiai (2018)
This paper proposes an experiment using a vapor generator for a low-temperature heat source to drive a turbine engine. The system consists of a heat source to heat the water in the vapor generator apparatus, and thus heating the water in the system of the working fluid increases the vapor turbine driving force. In this study, HCFC-141b is used as a working fluid in the system because it has better thermo-physical properties, is a non-flammable liquid, is non-destructive to the atmosphere, and has a high molecular mass and low boiling point. The experimental conditions comprised operating temperatures of 70 to 100°C and a starting temperature of 30°C. The variables studied were the heating rate of vapor generator, mass flow rate of the working fluid flow through the vapor generator, inlet and outlet temperatures and pressures through the flow vapor generator, and power output. These results were recorded to determine the performance and thermal efficiency of the vapor generator in the vaporized for driving the turbine. The results of this study show the potential of using a vapor generator for small-scale electricity production.